Naturally Occurred Fats and Oils: A Review - Chakraborti, Indranil (Asian Journal of Chemistry, 2010)
Fats and oils are categorized under the wide term lipids. They are found in abundance in vegetable and animal sources. They are glyceral esters of fatty acids. Both act as heat insulators and as reserve sources of energy.